Swimming performance of adults and copepodites of Caligus rogercresseyi against different water flow speeds in presence or absence of light and host fish attractants - Sievers, Gerold; Neumann, Joaquín (Austral Journal of Veterinary Sciences, 2024)
The present study was conducted to determine the swimming ability of adults and copepodites of Caligus rogercresseyi at three different water flow speeds, considering the presence or absence of attractants such as light and fish (Salmo salar). A total of 360 gravid females, 360 adult males, and 720 copepodites were randomly selected from a sea lice hatchery and distributed into groups. Each group was placed in a plastic bucket within a tank, and exposed or not to two attractants (light or host fish) at different water flow speeds (0, 1 and 2 cm/s). The results showed higher migration of adults and copepodites in the presence of light than in its absence (P < 0.05); however, no significant differences related to sea lice swimming performance were found in the presence or absence of fish (P > 0.05). Water flow speed had no effect on either variable (P > 0.05). In the current study, adult C. rogercresseyi demonstrated superior swimming capabilities compared with copepodites.